SEJARAH DEKONSENTRASI DI INDONESIA DAN AGENDA KEBIJAKAN KEDEPAN - W. Utomo, Tri Widodo (Pusat Pelatihan dan Pengambangan dan Kajian Desentralisasi dan Otonomi Daerah Lembaga Administrasi Negara, 2012)
Together with decentralization and assistance tasks (medebewind), deconcentration constitutes basic principles in managing central-local government relationship. From historical point of view, the degree of deconcentration and decentralization has been up and down. Until recently, there is no single believe among Indonesian experts and officials regarding the best form of deconcentration. Therefore, deconcentration continues to transform and still searching for its best formula. Under such consideration, this paper tries to tracking back the history of deconcentration and its limitations. Before coming to conclusion, it proposes four agendas to recover the implementation of deconcentration in Indonesia, i.e. clarifying the position of the head of region, improving election system, redisgning the deconcentration affairs and authorities, and explicating goals of decentralization and deconcentration.